(untitled) (Grande Medical Journal, 2019)
This is case report of a female with “A” sub type with acquired B antigen and non-secretor status, first ever reported with this combination in Nepal, during blood grouping of a sample of a patient with urinary tract infection. The patient was referred to our center for blood grouping, cross matching and transfusion due to severe anemia. During routine blood grouping, the red cells showed mixed field agglutination with anti-A, anti- AB and microscopic agglutination with anti-B. On serum grouping, we detected potent Anti-B and no agglutination with anti-A. There was no reaction with anti-A both at room temperature and at 37°C. Her cells were further tested with A1 Lectin and Anti-H antisera. There was strong reaction with A1 Lectin and 3+ macroscopic reaction with anti-H in addition to a positive auto-control. Her direct antiglobulin test was only +1 positive. For her “B” antigen, we acidified B antisera with HCl, which did not give any macro or microscopic agglutination with patient’s red cells. Her “Rh” status was positive and on examining the saliva, she was found to be non-secretor. The first choice of blood group for transfusion in this case is the “A1” sub type followed by “O” blood group. As the patient had already received “A” blood group and in the presence of auto antibodies, “A subgroup” blood transfusion should be avoided in her.